Working with abused children: Hobbs, CJ, Hanks, G I & Wynne, J M (1993) Child abuse and neglect: A clinician’s handbook. Edinburgh: Longman. - Collings, Steven (PINS-Psychology in Society, 2026)
This book is a practical and down-to-earth introduction to the major forms of abuse and neglect which fall under the broad umbrella of child maltreatment. Issues relating to the clinical presentation, differential diagnosis, and clinical management of child abuse and neglect are dealt with in a systematic, although somewhat cursory, fashion with separate chapters being given over to each of the major abuse categories.